THE INFLUENCE OF OCTAHEDRAL AND TETRAHEDRAL CATION SUBSTITUTION ON THE STRUCTURE OF SMECTITES AND SERPENTINES AS OBSERVED THROUGH INFRARED SPECTROSCOPY - Bishop J.; Murad E.; Dyar M.D. (My University, 2002)
Analysis of the near-infrared (NIR) spectral bands of phyllosilicates, together with the mid-infrared bands, enables testing and confirmation of band assignments for the structural OH vibrations. Spectral analyses of selected smectites and serpentine-kaolin minerals are presented here. The results of this study indicate that dioctahedral smectites may contain both in-plane and out-of-plane OH-bending vibrations, as suggested by Farmer (1974). In-plane bands occur near 800-915 cm-1, while the weaker out-of-plane vibrations occur near 600-700 cm-1 and are enhanced in dioctahedral smectites when the structure is disrupted by substitutions. Analysis of the OH-stretching vibrations and their NIR overtone bands is also presented for both smectites and serpentine-kaolin minerals. These overtones are more straightforward for serpentines than for kaolinite, and a strong overtone associated with the kaolinite OH-stretching band at 3620 cm-1 is found that supports its assignment as an OH-stretching band.
Keywords: infrared spectroscopy; smectites; serpentines; kaolinite; structural OH